2011
DOI: 10.1534/genetics.111.132118
|View full text |Cite
|
Sign up to set email alerts
|

Mendel’s Genes: Toward a Full Molecular Characterization

Abstract: The discipline of classical genetics is founded on the hereditary behavior of the seven genes studied by Gregor Mendel. The advent of molecular techniques has unveiled much about the identity of these genes. To date, four genes have been sequenced: A (flower color), LE (stem length), I (cotyledon color), and R (seed shape). Two of the other three genes, GP (pod color) and FA (fasciation), are amenable to candidate gene approaches on the basis of their function, linkage relationships, and synteny between the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 71 publications
1
61
0
7
Order By: Relevance
“…As GA is accumulated, the GA 20 -oxidase gene expression is reduced, and GA catabolism gene expression is enhanced [38][39][40]. In the mutant dwarf pea plants (le) [21,22] with a lack of GA due to reduced function of C3,β-oxidases the transcriptional activity of GA biosynthesis gene (GA20ox) is high, while it is low for GA deactivation gene (GA2ox). In the pea mutants SLN (SLENDER) with elongated shoots the disorders affect C2,β-oxidase gene.…”
Section: Growth Response In Mutant Plants Deficient In Gibberellin Bimentioning
confidence: 99%
“…As GA is accumulated, the GA 20 -oxidase gene expression is reduced, and GA catabolism gene expression is enhanced [38][39][40]. In the mutant dwarf pea plants (le) [21,22] with a lack of GA due to reduced function of C3,β-oxidases the transcriptional activity of GA biosynthesis gene (GA20ox) is high, while it is low for GA deactivation gene (GA2ox). In the pea mutants SLN (SLENDER) with elongated shoots the disorders affect C2,β-oxidase gene.…”
Section: Growth Response In Mutant Plants Deficient In Gibberellin Bimentioning
confidence: 99%
“…There are other candidate genes for characters in the pea genome, nonetheless still no solid evidence exists to say which of the alternative genes Mendel could have used in each particular case. A more complete review of these genes and other aspects of Mendel's work can be found in Ellis et al (2011) and Reid and Ross (2011).…”
Section: A318mentioning
confidence: 99%
“…However, given that his research built on the previous work of others and that we have some historical accounts of what mutants were available at the outset of his experiments in the 1850s (e.g., Knight 1799), we can make an educated guess in most instances (Reid & Ross 2011). Even harder than defining which seven loci Mendel studied is the question of which mutations he used.…”
Section: Mendel's Pea Genes Todaymentioning
confidence: 99%
“…Theoretically, it is now quite clear that there are many possible mutations in each gene that could produce the same phenotype, especially if Mendel's original mutation was a null. Again, the only way of determining this is to see what material would have been available in central Europe at the time that Mendel performed the studies (Reid & Ross 2011). With the improved linkage maps available today the seven traits in fact are thought to occupy only five of the seven linkage groups.…”
Section: Mendel's Pea Genes Todaymentioning
confidence: 99%
See 1 more Smart Citation